2018
DOI: 10.21273/hortsci12682-17
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard Floor Management and Cluster Thinning Inconsistently Affect ‘Pinot noir’ Crop Load, Berry Composition, and Wine Quality

Abstract: Growers of high-end ‘Pinot noir’ wine grapes (Vitis vinifera L.) commonly reduce yield by cluster thinning with the goal of increasing fruit quality; however, there are no objectively defined yield targets to achieve optimum fruit composition. Canopy leaf area relative to fruit yield can affect total soluble solids (TSS), and recommendations have been established for warm wine grape production regions. However, the relationship between leaf area and photoassimilation differs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…Crop loads below 7.2 did not result in an increase in juice soluble solids but did continue to increase vine size. This is consistent with other fruit thinning studies that showed little response of fruit maturation to crop load at Y:PW values below 10 and attribute fruit quality differences in this range to regional climatic conditions or seasonal variation (Keller M et al 2005, Preszler et al 2013, Reeve et al 2018). The crop load -Brix inflection point of 7.2 in this cool-climate study was slightly lower than the 10-12 reported in warmer climate studies (Kliewer and Dokoozlian 2005), supporting the theory that cool-climate grapevines need relatively more leaf area per unit fruit to reach maximum maturity.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Crop loads below 7.2 did not result in an increase in juice soluble solids but did continue to increase vine size. This is consistent with other fruit thinning studies that showed little response of fruit maturation to crop load at Y:PW values below 10 and attribute fruit quality differences in this range to regional climatic conditions or seasonal variation (Keller M et al 2005, Preszler et al 2013, Reeve et al 2018). The crop load -Brix inflection point of 7.2 in this cool-climate study was slightly lower than the 10-12 reported in warmer climate studies (Kliewer and Dokoozlian 2005), supporting the theory that cool-climate grapevines need relatively more leaf area per unit fruit to reach maximum maturity.…”
supporting
confidence: 90%
“…Several cool-climate crop load studies have questioned the appropriateness of these crop load indicators in regions where more leaf area per unit fruit may be needed to achieve optimum fruit maturity and vegetative growth (Howell 2001); however, these studies have provided little evidence to deviate from the general crop load response. Fruit thinning studies with Pinot noir in Oregon and Merlot in Hawkes Bay, New Zealand (Y:PW ranges 0.5 to 3.7 and 3.4 to 9.0, respectively) indicated excessive vegetative growth and canopy density in the fruiting zone as having a larger impact on fruit composition than crop load and questioned the need for fruit thinning at these values (King et al 2015, Reeve et al 2018. Riesling crop load studies in NY and WA (Y:PW ranges 2.9 to 9.9 and 8.2 to 11.4, respectively) both showed slight delays in fruit ripeness at the highest crop load levels but questioned if the minor improvement in fruit quality from fruit thinning justified the economic cost in labor and crop loss (Keller et al 2005, Preszler et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted on cluster thinning practices have applied variable yield reduction rates depending on cultivar. However, most research in Pinot noir has applied "half crop" treatments such as the one performed in the current study, removing all but the basal cluster on each fruiting shoot [34] or reducing cluster number by 50% [19].…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as climatic variation in growing season [21] and viticultural practices such as floor management [34], deficit irrigation [21,22], and leaf thinning [74,75] have all been found to have a greater effect on fruit composition than cluster thinning. Indeed, in the present study, no consistent effect of cluster thinning or cluster thinning timing was observed across two growing seasons, a cooler growing season and a warmer growing season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation